Beauty is in the Eye of the Beholder: The Impact of Organizational Identification, Identity, and Image on the Cooperative Behaviors of Physicians - Dukerich, Janet M.; Golden, Brian R.; Shortell, Stephen M. (Administrative Science Quarterly, 2002)
We use an established model of organizational identification to try to understand the voluntary cooperative behavior of professionals in organizations. We examined the relationships among physicians' assessments of the attractiveness of a health care system's perceived identity and construed external image, strength of system identification, and cooperative behaviors. We surveyed 1,504 physicians affiliated with three health care systems and collected follow-up data from 285 physicians a year later. Attractiveness of perceived identity and construed external image were positively related to physicians' identification with the system, which in turn was positively related to cooperative behavior. Extensions to the model of organizational identification are suggested.